Carbon and Nitrogen Metabolism Are Jointly Regulated During Shading in Roots and Leaves of Camellia Sinensis - Shao, Chenyu; Jiao, Haizhen; Chen, Jiahao; Zhang, Chenyu; Liu, Jie; Chen, Jianjiao; Li, Yunfei; Huang, Jing; Yang, Biao; Liu, Zhonghua; Shen, Chengwen (Frontiers in Plant Science, 2022)
Numerous studies have shown that plant shading can promote the quality of green tea. However, the association of shading with metabolic regulation in tea leaves and roots remains unelucidated. Here, the metabolic profiling of two tea cultivars (‘Xiangfeicui’ and ‘Jinxuan’) in response to shading and relighting periods during the summer season was performed using non-targeted metabolomics methods. The metabolic pathway analyses revealed that long-term shading remarkbly inhibit the sugar metabolism such as glycolysis, galactose metabolism and pentose phosphate pathway in the leaves and roots of ‘Xiangfeicui’, and ‘Jinxuan’ were more sensitive to light recovery changes. The lipid metabolism in the leaves and roots of 'Xiangfeicui' was promoted by short-term shading, while it was inhibited by long-term shading. In addition, the intensity of the flavonoid metabolites in the leaves and roots of ‘Jinxuan’ were upregulated with a trend of rising first and then decreasing under shading, and five flavonoid synthesis genes showed the same trend (F3H, F3'5'H, DFR, ANS, and ANR). Simultaneously, the amino acids of the nitrogen metabolism in the leaves and roots of the two cultivars were significantly promoted by long-term shading, while the purine and caffeine metabolism was inhibited in the leaves of ‘Xiangfeicui’. Interestingly, CsGS1.1 and CsTSΙ, amino acid synthase genes was upregulated in the leaves and roots of two cultivars. These results indicated that shading could participate in carbon and nitrogen metabolic regulation of both leaf and root, and root metabolism could have a positive association with leaf metabolism to promote the shaded tea quality.